The Lit de Justice of the Kings of France - Sarah Hanley (Princeton University Press, 2014)
ONE LOOK at the historical underpinnings of the Lit de Jmtice of the Kings of France recalls the Heraclitean paradox of "time and the river": one cannot "stand in the same place twice" amidst the fluvial tides of history. That paradox points to the epistemological dilemma which haunts these pages, where historical fictions and facts are sorted out. It is apparent that the fictive medieval origins of the Lit de Justice assembly were not produced by sixteenth-century rhetoricians, who were accused of valuing eloquence over truth, or by chroniclers, who were accused of weighting facts and fables equally. That fiction was deduced by historians, who consciously avoided the shifting sands of rhetorical prose and chronicle lore for the sure ground of ancient documents that were signed, dated, and deposited in archives. The fiction was turned into a legend by seventeenth-century historians, who conscientiously verified that documentary evidence and then contributed new sources to the thesis. And the legend was confirmed by eighteenth-century historians, who reviewed that history of the Lit de Justice in order to comprehend the pristine origins of the assembly. In early modern France the powerful force of historicism, nominalist and philological in conception, bred in its adherents a new mode of perception and a surety of purpose which shaped the mentalite of the times. Compiled through painstaking research, the corpus of knowledge about the Lit de Justice which they created offered a new way of apprehending reality, eventually assumed a truth of its own, and was passed to posterity with a scholarly imprimatur.Turning to the same paradox in the twentieth century, the problem of time and space is no less acute. It is still the puzzling task of cultural translation—the extraction of meaning from one system, the expression of it in another—which may at times confound historical explanation. As in the earlier centuries, this approach to the Lit de Justice is historical, but befitting the conceptual diversity of modern thought, history is given a helping hand here. The present reading of these events from various texts and contexts, gestures and symbols, suggests that French constitutional ideologies were propagated in Lit de Justice assemblies through legend, ritual, and discourse from the early sixteenth to the mid-seventeenth century while the historicist mentalite held sway. Repeating those historians of earlier centuries, though far less sure about apprehending reality, I have concluded also that the historical argument presented here now rests on its own.